2005
DOI: 10.22146/gamaijb.5581
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge as a Critical Resource in Innovation among Small Furniture Companies in Indonesia: An Exploration

Abstract: The furniture industry makes a significant contribution to the Indonesian economy but is exposed to an intensifying competitive environment and to emerging shortages of raw material. These circumstances have prompted small furniture manufacturers in the district of Jepara to undertake several types of innovation. It appears that of all first ranked innovations, product innovation is the largest category. In the overall pattern of innovations, market innovation and logistics innovation are also important, a sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…This finding corroborates previous similar studies on innovation among furniture and software firms in Indonesia (e.g. van Geenhuizen and Indarti, 2005;Indarti, 2010).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding corroborates previous similar studies on innovation among furniture and software firms in Indonesia (e.g. van Geenhuizen and Indarti, 2005;Indarti, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…The use of specific sources of knowledge is important for paticular innovations (Van Geenhuizen and Indarti, 2005). However, '... it was not sufficient to look independently at the various sources of information because the development and improvement of products and processes cannot depend only on one source of information, but they must rely on recourse to a variety of sources of information' (Amara and Landry, 2005:250).…”
Section: Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…These parties are plausible sources of knowledge which we expect to enhance a firm's innovativeness. For Indonesia, Van Geenhuizen and Indarti (2005) found that the degree of interaction between SMEs and various external parties might not be sufficiently developed, while the possible advantages of these relations have to date not been properly explored. External interaction entails a broader access to relevant know-how, possibilities to perform benchmarking activities, as well as opening new markets.…”
Section: Network: Parties Involved and Characteristicsmentioning
confidence: 99%
“…While the analysis of the performance impact of absorptive capacity is largely confirmed in the context of radical innovation (Pennings & Harianto, 1992;Corkburn & Henderson, 1998;Ahuja & Katila, 2001;Tsai, 2001) its relationship in the context of incremental innovation has not been given much attention in existing research. While there is no exact study which support of a positive relationship between absorptive capacity and incremental innovation performance in smaller firms, other studies (Bashkaran, 2006;van Geenhuizen & Nurul, 2005) found support for knowledge per se which impacts on incremental innovation in small firms. Therefore, to draw a differentiated picture of the innovation performance impact of absorptive capacity, this study tests the performance implications in terms of incremental innovation amongst Small-Medium Enterprises (SMEs) in Malaysia.…”
Section: Introductionmentioning
confidence: 96%